KEABSAHAN POLIS ASURANSI USAHA TANI PADI ANTARA KELOMPOK TANI BOJONG SARI DENGAN ASURANSI JASA INDONESIA (JASINDO) - Imam; Bahri Siregar, Syamsul (Universitas Wiralodra, 2020)
The agricultural sector is currently a sector that is synonymous with uncertainty because it depends on the season which negatively affects agricultural yields, and even farmers are at risk of crop failure and damage to agricultural infrastructure. This uncertainty concern, raises the need for insurance protection. However, there are different views on natural disasters between the Rice Farmers' Insurance Policy and Article 37 paragraph (2) of Law Number 19 of 2013 concerning Protection and Empowerment of Farmers. The research method in this study uses the juridical normative approach with data collection techniques by means of literature studies on legal materials, both primary legal materials, secondary legal materials and tertiary legal materials and field studies. The results showed that the Insurer is PT. Jasa Indonesia (Jasindo) as the sole implementer in collaboration with State-Owned Enterprises (BUMN) in providing premium subsidies, the insured is the Bojong Sari Farmer Group, Tempel Village, Lelea District, Indramayu Regency, West Java Province with the following Policy Number: 402.226. 110.19.0072 / 000/000. The insured object is rice in accordance with the Decree of the Minister of Agriculture Number 40 of 2015 concerning the Facilitation of Agricultural Insurance. Premium payments, namely from subsidized premium assistance by the Government as much as 80% and farmers bear as much as 20%. Compensation for agricultural product insurance, namely compensation given to participants in the Rice Farming Business Insurance in the event of a flood, drought and / or attack by plant pests. The coverage is set at Rp. 6,000,000 per hectare per planting season